High fetal risk in pregnancies of myositis patients—a Hungarian cohort study - Nagy-Vincze, Melinda; Szinay, Dorottya; Szabó, Katalin; Molnár Deliné, Sarolta; Balkay, László; Béldi, Tibor; Griger, Zoltán (Frontiers in Lupus, 2024)
Background Several systemic autoimmune rheumatic diseases may affect both fetal and maternal outcomes during pregnancy. However, little information is available regarding pregnancy outcomes in women with idiopathic inflammatory myopathy. Previously published articles stated that the activity of maternal disease may worsen pregnancy outcomes. A former multicenter study suggested that anti-Jo1 antibody positivity and joint involvement could distinguish a more vulnerable group regarding pregnancy complications. Our aim was to identify prognostic factors among clinical symptoms at disease onset and auto-antibody profiles for identifying a high-risk group for poor pregnancy outcome. Methods The clinical data of the myositis cohort of the Division of Clinical Immunology, University of Debrecen, Hungary, were reviewed retrospectively. IIM diagnoses were made by Bohan and Peter's criteria or European Alliance of Associations for Rheumatology/American College of Rheumatology (EULAR/ACR) criteria. Disease activity was evaluated based on physician opinion. Gynecological definitions were used to evaluate fetal outcomes. Results Reviewing clinical data of overall 763 patients (542 women and 221 men) revealed that 5.2% of female patients had pregnancies in the same time or after myositis onset. Among these, 71.4% of the mothers suffered from polymyositis (PM) and 28.6% suffered from dermatomyositis (DM). Their mean age at the time of myositis diagnosis was 25.28 years, and the average interval between myositis diagnosis and first pregnancy was 55.4 months. Maternal complications included preeclampsia in one case and pregnancy-induced myositis in 25% of cases. All cases of pregnancy-induced myositis improved after immunosuppressive treatment. Twenty-eight patients reported 60 pregnancies overall, with multiple pregnancies occurring in 57% of cases. Early or late fetal loss was detected in 41.7% of the pregnancies, and stillbirth occurred in 18.3% of deliveries. Although late fetal loss was observed mainly due to placental insufficiency in patients with anti-Jo1 positivity and complications seemed more frequent in PM cases, logistic regression analysis only confirmed that multiple pregnancies could be an independent risk factor for fetal (p = 0.0112) and interstitial lung disease of maternal complications (p = 0.02). Conclusion Internal organ involvement and the number of pregnancies could influence pregnancy outcomes in myositis patients. Patients’ family planning should be well organized and counseled by myositis experts. Prospective, multicenter collaborations are needed to precisely identify high-risk groups and state managing guidelines.